Efektivitas Penggunaan Video Youtube Dalam Mendukung Pembelajaran PKN, Terhadap Pengetahuan Moral Siswa Kelas IX Di SMPN 3 Percut Sei Tuan - Winda Arisandi; Agatha Sofia Margareta; Tri Santa Lasmarito; Jamaludin Rami; Sri Yunita (LPPM Politeknik Pratama, 2023)
The use of media that is less interesting, unpleasant and not easy for students to understand makes it difficult for students to understand the material and often feels bored and lacks motivation to learn. The aim of this research is to create interesting, adaptive YouTube video learning media that pays attention to student interests. As a Civics Teacher, you can build students' moral knowledge in YouTube videos. YouTube has the advantage of being very popular with all levels of Indonesian society, because of the presence of creators with varied content. YouTube contains audio-visual video content so that the messages contained in this content are very easily accepted by users or viewers. This research aims to determine the effectiveness of YouTube in supporting PPKn learning so that students' moral knowledge is formed. This research uses a questionnaire and quantitative methods. The answers of research respondents show that YouTube is effective as a PPKn learning medium.